2021
DOI: 10.1021/acsomega.1c04817
|View full text |Cite
|
Sign up to set email alerts
|

Designing of a Multi-epitope Vaccine against the Structural Proteins of Marburg Virus Exploiting the Immunoinformatics Approach

Abstract: Marburg virus disease (MVD) caused by the Marburg virus (MARV) generally appears with flu-like symptoms and leads to severe hemorrhagic fever. It spreads via direct contact with infected individuals or animals. Despite being considered to be less threatening in terms of appearances and the number of infected patients, the high fatality rate of this pathogenic virus is a major concern. Until now, no vaccine has been developed to combat this deadly virus. Therefore, vaccination for this virus is necessary to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 162 publications
2
44
0
Order By: Relevance
“… 111,112 During the prediction of spike glycoprotein epitopes, the server encompasses biological data of vaccine candidates. 111,113 Vary recent study Sami et al 114 used the VaxiJen server for assessing antigenicity of Marburg virus epitopes and they proposed a vaccine candidate that has the ability to generate an immune response against viral pathogenesis. The chemical and physical properties of the vaccine constructs were assessed by ExPASy.…”
Section: Discussionmentioning
confidence: 99%
“… 111,112 During the prediction of spike glycoprotein epitopes, the server encompasses biological data of vaccine candidates. 111,113 Vary recent study Sami et al 114 used the VaxiJen server for assessing antigenicity of Marburg virus epitopes and they proposed a vaccine candidate that has the ability to generate an immune response against viral pathogenesis. The chemical and physical properties of the vaccine constructs were assessed by ExPASy.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, EAAAK was employed to improve the bi-functional catalytic activity, give stiffness in addition to enhancing fusion protein stability (93). The second linker, GPGPG, was selected for its ability to induce HTL immune response and the ability to break the junctional immunogenicity, resulting in individual epitopes' restoration of immunogenicity (94). The final linker, KK, was employed because of its ability to bring the pH value close to the physiological range (95).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the epitopes, linkers, and adjuvant, the PADRE sequence was also added as it has been revealed that this sequence could minimize the polymorphism of HLA molecules in the population (96). Analyzing the results of the multitope vaccine assessment showed that, the current potential vaccine construct is antigenic with an antigenicity score of 1.07 which was more than the corresponding scores of the designed multitope vaccines against severe acute respiratory syndrome coronavirus 2 (97), Marburg virus (94), and Leptospira (98). Regarding the population coverage, the world coverage showed 100% for the constructed vaccine and that was similar to the corresponding coverage reported in (99).…”
Section: Discussionmentioning
confidence: 99%
“…By activating innate immunity cells and attracting naïve T cells through the chemokine receptor CCR-6, β-defensin peptides stimulate innate immunity cells ( 91 ). The maturation of dendritic cells, HTLs, CTLs, and IFN-γ-producing cells is induced by the 50S ribosomal protein L7/L12 when naive T-cells are stimulated ( 61 ). HBHA is a novel TLR4 agonist with minimal systemic toxicity, in addition to possessing a strong immunostimulatory potential and the potential to induce dendritic cells maturation in a TLR4-dependent manner ( 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…This server employs machine learning algorithms and a position-specific scoring matrix (PSSM) to predict epitope and assess immunological interactivities ( 60 ). The immunological simulation was carried out according to the procedure described elsewhere ( 61 ). For 1050 simulation steps (about 12 months), three in-silico doses were given at suggested 4-week intervals and at time steps of 1, 84, and 170 (one time step is 8 hours of everyday living).…”
Section: Methodsmentioning
confidence: 99%